[tex]\frac{3}{7} - \frac{1}{14} = \frac{6}{14} - \frac{1}{14}= \frac{5}{14}[/tex]
[tex]2\frac{5}{8} - \frac{9}{24} = \frac{21}{8} - \frac{9}{24} = \frac{63}{24} - \frac{9}{24} = \frac{54}{24} = 2\frac{6}{24} = 2\frac{1}{4}[/tex]
[tex]4\frac{5}{12} - \frac{2}{3} = \frac{53}{12} - \frac{8}{12} = \frac{45}{12} = 4\frac{9}{12} = 4\frac{3}{4}[/tex]
[tex]\frac{3}{4} +\frac{7}{16} = \frac{12}{16} + \frac{7}{16} = 1\frac{3}{16}[/tex]
[tex]4\frac{7}{9} + (\frac{4}{6} + \frac{1}{2}) = \frac{43}{9} + (\frac{4}{6}+\frac{3}{6} ) =\frac{43}{9} + \frac{9}{6} = \frac{86}{18} + \frac{27}{18} = 6\frac{5}{18}[/tex]